Clay-mediated selective hydrolysis of 5 `-O-acetyl-2 `,3 `-isopropylidene/cyclohexylidene nucleosides - Gurjar, Mukund K.; Mondal, Dhananjoy; Ravindranadh, S. V.; Chorghade, Mukund S. (Synthetic Communications, 2006)
A generalized procedure for the selective hydrolysis of 5'O-acetyl-2',3'-isopropylidene/cyclohexylidene nucleosides with a solid catalyst, Montmorillonite K-10 in refluxing methanol, to furnish 5'-O-acetyl-nucleosides is described.
Keywords: 5-O-acetylnucleosides; isopropylidene-nucleoside hydrolysis; montmorillonite K 10

Carbohydrate based approach towards the synthesis of aspercyclide C - Ramana, C. V.; Mondal, Mohabul A.; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A formal total synthesis of aspercyclide C (3) is described in which D-ribose is employed as a chiral pool material. The key step is a ring closing metathesis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: chiron approach; D-ribose; Mukaiyama reagent; ring closing metathesis (RCM); Ullmann coupling

Central core of uprolides D and E: a survey of some ring closing metathesis approaches - Ramana, C. V.; Salian, Sumanth R.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A preliminary study dealing with the feasibility of ring closing metathesis and ene-yne ring closing metathesis to construct the central bicyclic cores of uprolides D and E was investigated. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cembranolides; ene-yne metathesis; Ring closing metathesis; Sharpless asymmetric epoxidation; uprolides D and E

Carbohydrate templates for the synthesis of prototype renin inhibitors - Mohapatra, Debendra K.; Sahoo, Gokarneswar; Sankar, Kuppusamy; Gurjar, Mukund K. (Tetrahedron-Asymmetry, 2008)
A concise synthesis of a prototype renin inhibitor and its 7-epimer has been accomplished starting from readily available D-glucose. (C) 2008 Elsevier Ltd. All rights reserved.

Carbohydrate based total synthesis of xestodecalactone B and C: revision of the absolute configuration - Pal, Rita; Rahaman, Hasibur; Gurjar, Mukund K. (Current Organic Chemistry, 2012)
A convergent chiral pool approach for the total synthesis of xestodecalactones B and C was demonstrated in which intramolecular acylation reaction constituted the key step. Synthetic and spectroscopic studies reported herein, suggested that the previously assigned structures of xestodecalactone B and C be interchanged.
Keywords: Chiral pool; Hydroboration; Intramolecular acylation; Pinnick oxidation; Revision of absolute configuration; Xestodecalactone B and C

Carbohydrate-based synthesis of the C13-C22 fragment of amphidinolide X - Gurjar, Mukund K.; Yellol, Gorakh S.; Mohapatra, Debendra K. (European Journal of Organic Chemistry, 2012)
A facile carbohydrate-based route was developed for the synthesis of the tetrahydrofuran (C13C22) fragment of amphidinolide X. Starting from L-sorbose, the key reactions followed include the stereoselective synthesis of a quaternary center at C1, BartonMcCombie deoxygenation at C2, Mitsunobu inversion at C3, and chain elongation by a Wittig reaction at C5.
Keywords: Cytotoxicity; Macrolides; Mitsunobu inversion; Natural products; Wittig reactions